Colorimetric Assay for Uracil DNA Glycosylase Activity Based on Toehold‐Mediated Strand Displacement Circuit. Issue 3 (8th November 2019) - Kim, Youna; Park, Yeonkyung; Lee, Chang Yeol; Park, Hyun Gyu
Abstract: Herein, a novel enzyme‐free and label‐free strategy for colorimetric assay of uracil DNA glycosylase (UDG) activity, which relies on a target‐activated toehold‐mediated strand displacement (TMSD) circuit is described. The strategy employs a detection duplex probe composed of a uracil‐containing strand (US) and a catalyst strand (CS). UDG present in a sample will cleave uracil bases within US and destabilize the detection duplex probe, which then leads to the dissociation of the detection duplex, releasing CS. The free CS promotes the TMSD reaction, consequently liberating a G‐quadruplex DNAzyme strand (GS) which is initially caged by a blocker strand (BS). Notably, a fuel strand (FS) is supplemented to recycle the CS to promote another cycle of TMSD reaction. As a consequence, a large number of GSs are activated by UDG activity and a distinct colorimetric signal is produced through the oxidation of ABTS promoted by the peroxidase mimicking activity of the liberated GSs. Based on this design principle, UDG activity down to 0.006 U mL −1 with excellent selectivity is successfully determined. The practical applicability of this assay is also demonstrated by reliably determining UDG activities in human serum. Abstract : Herein, a novel enzyme‐free and label‐free colorimetric assay for uracil DNA glycosylase activity which relies on target‐triggered toehold‐mediated strand displacement reaction is developed.